Microalgae at wastewater pond treatment in cold climate : an ecological engineering approach - Grönlund, Erik (Luleå tekniska universitet, 2004)
Three types of wastewater ponds in subarctic climates were investigated, each of them highly dependent on microalgae. They were fellingsdams, i.e. wastewater stabilization ponds complemented with chemical precipitation, high-rate algal ponds (HRAPs), and a type of aquaculture interface ponds between a wastewater treatment plant and the natural surrounding. From a microalgae taxa perspective green algae and cryptophytes were dominant in the wastewater ponds. Green algae and cryptophytes were also, together with chryso- and haptophytes, dominating the hypereutrophic and eutrophic stages of the natural lakes. Biomasses in the different types of ponds were of very different order of magnitude. From 100-1000 mg/l in the stabilization ponds during summer and 10-100 mg/l in spring and autumn, 70- 90 mg/l in a HRAP in autumn, to 5-30 mg/l in the most hypereutrophic stage in the natural ponds, 1-10 mg/l in the eutrophic stage, and below 1 mg/l in the oligotrophic stage. The connection between wastewater pond treatment and the field of ecological engineering was recognized. Future development of pond technology may benefit from a stronger connection to the theoretical framework of systems ecology developed in collaboration with the field of ecological engineering and ecotechnology. Godkänd; 2004; 20061005 (ysko)